Fast handover technique in heterogeneous wireless networks - Abdullah, Radhwan Mohamed (2014)
The next generation of wireless communication systems are facing many challenges that need solutions so that it can coexist with each other. One of these challenges is the mobility solutions that facilitate users with seamless inter-technology roaming capabilities that in turn require a seamless inter-system handover. Naturally, every inter-system roaming which leads to vertical handover requires that both link layer and network layer handovers happen, since network point of attachment as well as the device interface is changed. Several investigations and efforts in standardization are being made by several institutes and individuals to finally design and implement each of these communication layers. However, for the specific purpose of vertical handover in a heterogeneous wireless network, the information preparation for these two layers before any operations of handover can directly affect the significant performance parameters and consequently lead to seamless handover. This thesis is intended for detailing out a study of vertical handover in a heterogeneous wireless network that includes two main aspects. These aspects are the network information gathering and then the use of these information during the vertical handover. First, we proposed an Enhance Access Router Discovery (EARD) method for exchanging the information between the access routers that overlap in the coverage area. The gathered information includes a list of unique IP addresses that are generated and checked by their access router, the media access control (MAC) address of the device, channel number and additional information related to the network characteristics and requirements. Second, the use of these information to support all the handover operations, which includes network discovery, handover decision and handover execution. In the first operation, the previous access router provides information about the neighboring networks for Mobile Node (MN) to discover available networks as soon as possible. The second operation is selecting the best available network for MN through the network side and taking into consideration the traffic type. The last operation, the previous access router rapidly provides a unique Ipv6 address instead of new access router for MNs to execute the last operation of handover. The results show the benefits of our EARD method by improving the discovery time of networks, giving the best performance in terms of network selections and minimizing the handover latency and packet loss in handover execution when compared to the conventional technique.